ER stress and unfolded protein response in amyotrophic lateral sclerosis—a controversial role of protein disulphide isomerase - Jaronen, Merja; Goldsteins, Gundars; Koistinaho, Jari (Frontiers in Cellular Neuroscience, 2014)
Accumulation of proteins in aberrant conformation occurs in many neurodegenerative diseases. Furthermore, dysfunctions in protein handling in endoplasmic reticulum (ER) and the following ER stress have been implicated in a vast number of diseases, such as amyotrophic lateral sclerosis (ALS). During excessive ER stress unfolded protein response (UPR) is activated to return ER to its normal physiological balance. The exact mechanisms of protein misfolding, accumulation and the following ER stress could lead to neurodegeneration and the question whether UPR is a beneficial compensatory mechanism slowing down the neurodegenerative processes are of interest. Protein disulphide isomerase (PDI) is a disulfide bond-modulating ER chaperone, which can also facilitate the ER-associated degradation (ERAD) of misfolded proteins. In this review we discuss the recent findings of ER stress, UPR and especially the role of PDI in ALS.